Influence of different methods for classification of lymph node metastases on the survival of patients with oral squamous cell carcinoma - Tomo, Saygo [UNESP]; de Castro, Tamara Fernandes [UNESP]; Araújo, Winicius Arildo Ferreira [UNESP]; Collado, Francisco Urbano [UNESP]; Neto, Sebastião Conrado [UNESP]; Biasoli, Éder Ricardo [UNESP]; Bernabé, Daniel Galera [UNESP]; Miyahara, Glauco Issamu [UNESP] (Elsevier, 2023)
Background: Despite the advances in the classification of oral squamous cell carcinoma (OSCC) based on its extension by the TNM system, there is still a need for methods to better classify the patients to predict prognosis and indicate adjuvant therapy. Objectives: To analyze the influence of the number of positive lymph nodes (PN), lymph node ratio (LNR), and log odds of positive lymph nodes (LODDS) in survival of patients with OSCC. Methods: Clinicopathologic data from patients with OSCC who were treated with curative purposes by surgery and neck dissection (ND) with or without subsequent adjuvant therapies from 1991 to 2015 was retrospectively assessed. The impact of the PN, LNR, LODDS, and other variables on overall survival (OS) and disease-free survival (DFS) was analyzed in univariate and multivariate analyses. Results: One hundred nineteen patients were included in this study. In the univariate analysis the PN had a significant impact on OS (p = 0.001) and DFS (p = 0.020), and the LNR had a significant impact on the OS (p = 0.042). In the multivariate analysis with other relevant clinicopathologic variables, the PN was the only significantly independent factor influencing in the OS (p = 0.017) but not in DFS (p = 0.096). Conclusions: The PN is an independent prognostic indicator for OS and DFS in patients with OSCC and has the potential to aggregate the current AJCC classification. The LNR has potential to be an important prognostic indicator, but the methods for this classification require lapidation. The LODDS did not demonstrate prognostic potential.
Keywords: Lymphatic metastasis; Oral cancer; Oral squamous cell carcinoma; Prognostic factors